2007
DOI: 10.1165/rcmb.2006-0400oc
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Regulates Cilia Loss and foxj1 Expression in Human Airway Epithelium

Abstract: Mucociliary clearance is essential to the defense mechanisms of the respiratory system. Loss of normal mucociliary clearance contributes to the pathogenesis of genetic and acquired lung diseases. Treatment of cultured differentiated human airway epithelial tissue with IL-13 resulted in a loss of ciliated epithelial cells and an increase in mucus-secreting cells. The loss of ciliated cells was characterized by mislocation of basal bodies and loss of ezrin from the apical cell compartment. In addition to the los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
66
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 49 publications
14
66
0
Order By: Relevance
“…This would suggest that it is via an IL-13 independent effect that our asthmatic cultures are differentiating to this phenotype, which we are currently investigating. The origins of goblet cells are not well understood, although Clara cells (31) and ciliated cells (20,32) have been implicated as goblet cell progenitors, which might explain the increase in goblet cell numbers in our asthmatic cultures. We cannot completely exclude that the difference in unstimulated asthmatic cultures is because of a "carry-over effect" from IL-13 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This would suggest that it is via an IL-13 independent effect that our asthmatic cultures are differentiating to this phenotype, which we are currently investigating. The origins of goblet cells are not well understood, although Clara cells (31) and ciliated cells (20,32) have been implicated as goblet cell progenitors, which might explain the increase in goblet cell numbers in our asthmatic cultures. We cannot completely exclude that the difference in unstimulated asthmatic cultures is because of a "carry-over effect" from IL-13 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in DUOX1/2 promoter regions are consistent with the highly variable transcriptional regulation of airway epithelial DUOX1 and DUOX2 in response to pro-inflammatory cytokines or to bacterial or viral stimuli (36,83,96). For example, DUOX1 mRNA expression in primary airway epithelial cultures is induced 3-5 fold by the Th2 cytokines interleukin (IL)-4 and IL-13 (83), which induce ciliatedto-mucus cell transdifferentiation and mucus hyperplasia during allergic airway inflammation (97,98). DUOX1 expression is also dramatically enhanced after hormonal differentiation of fetal lung epithelial cells to alveolar type II cells (90).…”
Section: Nadph Oxidases Within the Airway Epithelium: Duox1 And Duox2mentioning
confidence: 99%
“…Despite their postmitotic state (35)(36)(37), ciliated cells are known to change their shape and gene expression during airway repair (38), suggesting that their behavior may depend on the specific type of injury model used in any given study. Evidence for transdifferentiation of ciliated to mucous cells after IL-13 treatment (23,24), or to squamous cells after naphthaleneinduced injury (38), has been reported. Indeed, a recent study used a lineage tracing strategy in vitro, and suggested that FoxJ1-Cre; EGFP cells give rise to goblet cells in an air-liquid interface platform of epithelial cultures (24).…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of Sendai virus infection, epidermal growth factor receptor (EGFR) activation in ciliated cells inhibited apoptosis and led to the expression of goblet cell markers in these ciliated cells (22). The presence of cells possessing characteristic markers of both ciliated and mucous cells in the mouse and human airway epithelium, in vivo and in vitro, led the authors to postulate that ciliated cells transdifferentiate into mucous cells after IL-13 treatment (22,23). Very recently, Turner and colleagues (24) also suggested that ciliated cells could convert to goblet cells using human airway epithelial cells in culture.…”
mentioning
confidence: 99%